Başarılı Şirket Küçülmeleri - (:unkn) unknown (My University, 2002)
0

Recently, many organizations are downsizing due to globalization, increased competition and technological developments. It is important that organizations plan all the steps before they implement the downsizing. The communication between the top management and employees should be open. Management should not overlook the needs of employees staying in the organization during downsizing because these people would make up the workforce that would pay an important role in the success of the organization in the future.